Granulosa cell tumor of the ovary associated with Endometrial Cancer - Nayak, Neha; Vaidya, Sapana Amatya (Nepalese Journal of Cancer, 2024)
Sex cord–stromal tumors (SCST) of the ovary comprise 5% to 8% of all ovarian malignancies. Granulosa cell tumors (GCT) are the most common type of malignant ovarian SCST accounting for 2% to 5% of all ovarian malignancies. Most tumors secrete estrogen. This can lead to an estrogen dependent endometrial hyperplasia and in some cases endometrial cancer. We report the case of a 62 year old woman with endometrial adenocarcinoma and adult granulosa cell tumor of the ovary who presented with postmenopausal bleeding and adnexal mass. She underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy, infracolic omentectomy, and pelvic lymphadenectomy, and the specimen was submitted for histopathological examination. Concomitant adult GCT and endometrial Cancer is rare. This diagnosis requires a high index of suspicion along with imaging and histopathology.